Extração de Obstruções Perspectivas de Edifícios ao Longo de Vias Urbanas - Fazan, Antonio Juliano [UNESP] (2006)
This paper presents an approach for extraction of perspective obstructions in high-resolution aerial images caused by the perspective projection of buildings onto adjacent urban ways. The proposed methodology consists in firstly extracting the contours of building roofs and urban ways from an intensity image generated by a conversion of a Digital Elevation Model (DEM). In the following, the polygons representing the roof contours are projected through the perspective bundle onto the respective mean planes of adjacent ways. Intersections between polygons representing roof contours and local segments of adjacent ways allow the extraction of the perspective obstructions in the object-space. The perspective obstruction polygons are finally projected onto the digital image basically using the collinearity equations. The results obtained by methodology allow the verification of its performance and show its potential for extraction of perspective obstructions in high-resolution aerial images.